THE ERBIL PLAIN ARCHAEOLOGICAL SURVEY: PRELIMINARY RESULTS, 2012–2020. (December 2021) - Ur, Jason; Babakr, Nader; Palermo, Rocco; Creamer, Petra; Soroush, Mehrnoush; Ramand, Shilan; Nováček, Karel
Abstract : The Erbil Plain Archaeological Survey (EPAS) investigates settlement and land use from the Neolithic to the present in the Erbil Governorate of the Kurdistan Region of Iraq, which includes a large portion of the core of the Assyrian Empire. In seven field seasons, it has documented a broad settlement landscape in a region of great social and political importance, especially in the Bronze and Iron Ages, including 728 archaeological sites. Its field methodology combines traditional surface collection with the use of historical aerial and satellite photographs, mobile GIS, and UAV (drone) photogrammetry. Preliminary results show some unexpected patterns: a high density of culturally Uruk settlements in the fourth millennium B.C., variable urban morphologies in the Early Bronze Age; and large but low-density settlements at the end of the Sasanian period or the early Islamic period. The project is explicitly testing several hypotheses about centralized Neo-Assyrian landscape planning in the imperial core. These hypotheses appear to be confirmed, although the situation was more complex than in surrounding provinces, probably due to the longer history of continuous settlement.